2022
DOI: 10.1186/s12884-022-04593-3
|View full text |Cite
|
Sign up to set email alerts
|

Community food beliefs during pregnancy in rural kebeles of Ofla Woreda, Northern Ethiopia: an explorative qualitative study

Abstract: Background Dietary related misconceptions during pregnancy affect the heath of mothers and their growing babies. Misconceptions vary from place to place and from community to community. Understanding of a given community’s food perceptions during pregnancy helps policy makers able to design cultural appropriate interventions. In Ethiopia, however, evidences on food beliefs and perceptions during pregnancy are limited. Therefore, this study is aimed at qualitatively assessing community food beli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In Ethiopia, dietary diversity is generally limited by low consumption of animal source foods, fruits, and vegetables [ [26] , [27] , [28] , [29] ]. In the Amhara region, consumption is further restricted due to cultural and religious practices such as the absence of snacks between meals, heavy workloads forcing people to skip meals, and prolonged religious fasting seasons [ [30] , [31] , [32] ]. Participants emphasized that pregnant women are encouraged to fast unless they have health issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ethiopia, dietary diversity is generally limited by low consumption of animal source foods, fruits, and vegetables [ [26] , [27] , [28] , [29] ]. In the Amhara region, consumption is further restricted due to cultural and religious practices such as the absence of snacks between meals, heavy workloads forcing people to skip meals, and prolonged religious fasting seasons [ [30] , [31] , [32] ]. Participants emphasized that pregnant women are encouraged to fast unless they have health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Tella , a traditional fermented alcoholic drink, resembles a beer with an estimated alcohol content between 2% and 6% depending on the fermentation and raw material used [ 35 ]. Previous studies have shown that alcohol consumption during pregnancy increases risk of adverse birth outcomes, particularly preterm delivery and low birth weight [ 32 , 36 ]. Fetal alcohol syndrome is a consequence of prenatal alcohol consumption that leads to neurocognitive deficits, growth deficiency, and facial dysmorphology in the unborn child [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tafese et al [ 53 ] observed stunting, underweight, and wasting in 42.0%, 24.6%, and 14.5%, respectively, of 12–36-month-old children in relationship with the maternal ‘Tella’ intake. Eyasu et al [ 54 ] studied that the perceived benefits (without scientific basis) of Ethiopian women and the rest of the population were that, for example, the intake of ‘Tella’ is beneficial to ‘hydrate’ the body of pregnant women and ‘clean’ the fetus and the uterus before and during pregnancy. Debele et al [ 55 ] suggested that there is another reason argued by the Ethiopian community and alcohol sellers, which is that it eases their parenting duty and that the introduction of consumption of these beverages in children after six months is used so that they sleep while the mothers are gone for a long trip or to the market.…”
Section: Discussionmentioning
confidence: 99%
“…While this literature is diverse, key factors shaping the choice of UPF highlighted include convenience and widespread availability; these foods' relative affordability; and social desirability and shifting tastes. In Ethiopia, previous qualitative investigations related to nutrition and diet have centred around nutritional practices and taboos for adult women during pregnancy rather than examining IYCF practices, concluding that it is common for pregnant women to avoid certain foods (particularly animal‐source foods) and restrict portions (Demilew et al, 2020 ; Eyasu et al, 2022 ; Tesfa et al, 2023 ; Wondmeneh, 2022 ; Zerfu et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%